PEMIKIRAN KRITIS SOUND GOVERNANCE TERHADAP GLOBALISASI: PANDANGAN DARI ALI FARAZMAND - Faturahman, Burhanudin Mukhamad (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2019)
Globalization is an ideology that contributes directly to governance, especially in developing and under developing countries. The governance system suggested by the global elite, namely good governance that transcends the territorial boundaries of the state, is allegedly causing uncertainty at local, national and regional governance levels. According to Ali Farazmand the dimension in sound governance seeks to organize the structure, norms, clear values of management and public administration amidst the diversity and rapid changes in the international environment.